2020
DOI: 10.1101/2020.04.03.024257
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

SARS-CoV-2 and SARS-CoV differ in their cell tropism and drug sensitivity profiles

Abstract: 18 SARS-CoV-2 is a novel coronavirus currently causing a pandemic. We show 19 that the majority of amino acid positions, which differ between SARS-CoV-2 and the 20 closely related SARS-CoV, are differentially conserved suggesting differences in 21 biological behaviour. In agreement, novel cell culture models revealed differences 22between the tropism of SARS-CoV-2 and SARS-CoV. Moreover, cellular ACE2 23(SARS-CoV-2 receptor) and TMPRSS2 (enables virus entry via S protein cleavage) 24 levels did not reliably in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
91
1
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(98 citation statements)
references
References 84 publications
3
91
1
2
Order By: Relevance
“…We identified 14 key studies that detailed the antiviral activity of 72 compounds [23][24][25][26][27][28][29][30][31][32][33][34][35][36][37] Table 1.…”
Section: Identified Papers and Methodsmentioning
confidence: 99%
“…We identified 14 key studies that detailed the antiviral activity of 72 compounds [23][24][25][26][27][28][29][30][31][32][33][34][35][36][37] Table 1.…”
Section: Identified Papers and Methodsmentioning
confidence: 99%
“…To establish cell culture systems for studying SARS-CoV-2 replication and host cell responses, we examined the epithelial lung cancer cell lines, H1299 and Calu-3, as well as the epithelial colorectal adenocarcinoma cell line, Caco-2, which is frequently used as a coronavirus cell culture model [30][31][32]. Transfection of poly-I:C RNA, resulted in induction of IFIT1, IFIT2 and OAS2 (2'-5'-Oligoadenylate Synthetase 2) genes in Calu-3 and H1299 cells, indicating sensing of cytoplasmic foreign RNA is active in these cell types.…”
Section: Different Permissiveness Of Sars-cov-2 Infection In Cell Linesmentioning
confidence: 99%
“…A recent report highlighted the potential of prazole compounds to have a therapeutic effect on SARS-CoV-2 when combined with remdesivir (30). However, the authors did not definitively identify the mechanism of action of the prazoles and also concluded that the potency of the prazole compound used, omeprazole, is too low to reach therapeutic levels in vivo.…”
Section: Discussionmentioning
confidence: 99%
“…Recent reports indicate that drugs from the prazole family, including tenatoprazole and esomeprazole, form a disulfide linkage to Tsg101, which results in blocking the release of HIV-1 from cells in culture (5). Other groups recently reported that prazoles may have potential as an antiviral therapeutic in HSV and SARS-CoV2 in combination with acyclovir or remdesivir, respectively (29,30). However, the prazole compound used in these studies, omeprazole, was not potent enough to be predicted to have a therapeutic effect in vivo.…”
Section: Introductionmentioning
confidence: 99%